Respuesta :
When solving these types of questions, we need to find the value of x and y. The only way to do this is to solve.
Take the value of the first equation: x = 1 + 3y and plug it into the second equation.
2(1+3y) - 5y = 3
2 + 6y - 5y = 3
2 + y = 3
y = 1
We know what y equals but we still need to know what x would equal to.
x - 3y = 1
x - 3(1) = 1
x - 3 = 1
x = 4
(x,y) or (4,1)
So, now we obviously have our answer, and I really hope my explanation helped.
Answer would be (4,1)
Take the value of the first equation: x = 1 + 3y and plug it into the second equation.
2(1+3y) - 5y = 3
2 + 6y - 5y = 3
2 + y = 3
y = 1
We know what y equals but we still need to know what x would equal to.
x - 3y = 1
x - 3(1) = 1
x - 3 = 1
x = 4
(x,y) or (4,1)
So, now we obviously have our answer, and I really hope my explanation helped.
Answer would be (4,1)